MAD* Beyond Defence - Gitanjali Adlakha-Hutcheon (The Journal of Intelligence, Conflict and Warfare, 2022)
Advancements in technology are regularly identified, assessed, and classed into emerging and/or potentially disruptive technologies, according to their ability to cause disruptions to defence systems, and in defence. Perhaps this is because defence capabilities centre on grand technology systems deployed at the level of nations. Hypersonic missiles are one example. The testing of a new hypersonic missile or a research program on types of hypersonic drones immediately sparks questions like: which other nations have such capability? or what types of technologies can be used to detect or counter these? In contrast, the ability to identify weak, faint factors that add up and lead to conflict are not brought together in a systematic manner. Nor is it common for there to be a cross-talk between a combination of methods used within military science and technology organizations over in to social sciences related to intelligence and/or conflict. This is a preventable strategic foresight issue relevant for enhancing, planning for, and investing in the security space. This paper describes the MAD (Methodology for Assessing Disruptions) tool, which is adaptable beyond the defence domain. MAD is a scenario-based two-part table-top exercise conducted to identify weak signals that have the potential to cause disruptions, which by consequence may coalesce into challenges for security. Exercising such methods is essential for security professionals to prepare and plan for future conflicts instead of constantly reacting to immediate acute problems.